Revisiting the Transcriptome Landscape of Pig Embryo Implantation Site at Single-Cell Resolution - Tian, Qing; He, Jia-Peng; Zhu, Can; Zhu, Qiu-Yang; Li, Yu-Gu; Liu, Ji-Long (Frontiers in Cell and Developmental Biology, 2022)
Litter size is one of the most economically important traits in commercial pig farming. It has been estimated that approximately 30% of porcine embryos are lost during the peri-implantation period. Despite rapid advances over recent years, the molecular mechanism underlying embryo implantation in pigs remains poorly understood. In this study, the conceptus together with a small amount of its surrounding endometrial tissues at the implantation site was collected and subjected to single-cell RNA-seq using the 10x platform. Because embryo and maternal endometrium were genetically different, we successfully dissected embryonic cells from maternal endometrial cells in the data according to single nucleotide polymorphism information captured by single-cell RNA-seq. Undoubtedly, the interaction between trophoblast cells and uterine epithelial cells represents the key mechanism of embryo implantation. Using the CellChat tool, we revealed cell-cell communications between these 2 cell types in terms of secreted signaling, ECM-receptor interaction and cell-cell contact. Additionally, by analyzing the non-pregnant endometrium as control, we were able to identify global gene expression changes associated with embryo implantation in each cell type. Our data provide a valuable resource for deciphering the molecular mechanism of embryo implantation in pigs.